Menggali Potensi Sumber Pendapatan Asli Daerah Kabupaten Pegunungan Arfak Provinsi Papua Barat Melalui Analytical Hierarchy Process (AHP) - Muhammad Guzali Tafalas (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
The Arfak Mountains Regency is administratively formed in 2012. With the establishment of the Arfak Mountains District as a new autonomous region, all forms of economic levels have been separated from the former regency. Arfak Mountains Regency as an autonomous region is expected to have the ability to manage regional own revenue to finance the administration of the regional government. In achieving the capability in regional financial independence, it is necessary to optimize the sources of regional revenue. The results of the Analytical Hierarchy Process (AHP) on the assessment of several alternative policies related to the optimization of sources of regional own revenue in the Arfak Mountains District, are as followed: (1). Increasing revenue capacity through better planning; (2). expanding revenue bases; (3). improving administrative efficiency and reducing collection costs; (4). strengthening collection processes and (5). improving controlling processes. The success of the management of regional own revenue is not only measured by the amount of revenue that can be achieved, but also by the extent to which the regional own revenue can play a role in driving the economy of the community so that it can improve the welfare of the community in this regency.